(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
This project examines the use of GIS and Remote Sensing in evaluating Greenery Reduction in Ibadan between 1972 and 2016 so as to detect magnitude of the changes that has taken place between these periods. Subsequently, the implications of foliage reduction on Temperature to determine heat island within Ibadan and used the result to suggest on how to sustain the Metropolis. In achieving this, imageries of 1972, 1984, 2000 and 2016 were classified into five classes which are Less built-up, Dense built-up, Light Forest, Dense Forest and Water. The quantitative assessment of the change shows a rapid growth in Less built-up features between 1972 and 1984 while between the period of 1984, 2000 and 2016 Light forest witnessed rapid reduction. Thermal Band of 2000 Landsat7 imagery and 2016 Landsat8 imagery were explored for Land Surface Temperature using NDVI to determine strength of vegetation. Further analysis was done on Global Weather data to see the effect of Temperature and the Rate of Precipitation on greeneries. The inference of this project is that degradation of vegetation cover is a determinant to Urban Heat Island (UHI). It was therefore suggested that there is need for proper planning and planting of trees so that Development will continue without hampering living in Ibadan.